PENGELOLAAN SUMBER DAYA MANUSIA WIDYAPRADA DI LEMBAGA PENJAMINAN MUTU PENDIDIKAN KALIMANTAN BARAT - Sukowati, Endang; Wahyudi, Wahyudi; Chiar, H.M. (Universitas Tanjungpura, 2022)
AbstractThe purpose of this research in general is to obtain accurate information about themanagement of widyaprada human resources in LPMP West Kalimantan. This study usesa descriptive method with a qualitative approach. Data collection techniques usinginterviews, observation and documentation. The results of the study are 1) that theWidyaprada human resource planning at LPMP West Kalimantan refers to and is guidedby central policies. 2) the implementation of Widyaprada human resource managementat LPMP West Kalimantan has been running smoothly following the applicableregulations. 3) evaluation of Widyaprada's human resource management is carried outand received at the beginning of each year (evaluation in 2020 is carried out in early2021) in the form of SKP. 4) The obstacle in managing Widyaprada's human resourcesat LPMP West Kalimantan is if there is a sudden change in policies and rules while workactivities are in progress. 5) Efforts to overcome obstacles in managing Widyaprada'shuman resources at LPMP West Kalimantan are by working solidly as a team, conductinginternal analysis, coordinating and communicating with the central party.Keyword: Management, Human Resources, Widyaprada.